2017
DOI: 10.1016/j.jad.2017.03.045
|View full text |Cite
|
Sign up to set email alerts
|

Nice guys: Homozygocity for the TPH2 -703G/T (rs4570625) minor allele promotes low aggressiveness and low anxiety

Abstract: Subjects with the TPH2 rs4570625 TT genotype, especially males, exhibit less aggression and a favourable impulsivity profile, and develop anxiety disorders by young adulthood less often.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 45 publications
4
22
1
1
Order By: Relevance
“…Our results indicate the possibility that the GG allele variant previously associated with lower risk for depression (Gao et al., ) also may play a role in positive emotional development, fitting the transactional model of child positive affects suggested by Davis and Suveg (). However, in a recent study, the TT genotype was associated with a more favorable outcome by young adulthood, especially in males (Laas et al., ). Further studies are needed, as the role of genes in child psychological development has proven to be quite complex.…”
Section: Discussionmentioning
confidence: 91%
“…Our results indicate the possibility that the GG allele variant previously associated with lower risk for depression (Gao et al., ) also may play a role in positive emotional development, fitting the transactional model of child positive affects suggested by Davis and Suveg (). However, in a recent study, the TT genotype was associated with a more favorable outcome by young adulthood, especially in males (Laas et al., ). Further studies are needed, as the role of genes in child psychological development has proven to be quite complex.…”
Section: Discussionmentioning
confidence: 91%
“…to action with less forethought than risk-free, but high Maladaptive impulsivity has high harm risk while Adaptive impulsivity supports success by agility. Previously, AMIS has been applied in a series of studies on risk-taking behaviour and impulsivity-related candidate genes studies, and found to have good predictive validity (e.g., Eensoo et al, 2004;Paaver et al, 2006;Laas et al, 2015a;Laas et al 2015b;Laas et al, 2017;Luht et al, 2019) At age 25, the Mini-International Neuropsychiatric Interview (MINI.5.0.0), (Sheehan et al, 1998) Estonian version (Shlik et al, 1999) Likert scale questions about misprize within the family and about emotional and physical abuse (Paaver et al, 2008;Kiive et al, 2010).…”
Section: Samplementioning
confidence: 99%
“…In this study, the opposite association between higher ELS and increased brain volumes observed in the TPH2 rs4570625TT homozygotes contrasts with previous reports on a genetic susceptibility for pronounced ELS-associated brain structural deficits. While some studies that combined the low-frequency TPH2 rs4570625 T-carrier groups initially revealed increased psychopathological risk (Gao et al 2012), anxiety-associated traits (Gutknecht et al 2007) and detrimental effects of ELS (Mandelli et al 2012;Forssman et al 2014), accumulating evidence indicates that TT homozygotes differ from both other variants in terms of lower anxiety-related behavior and psychopathological risk (Reuter et al 2007;Lehto et al 2015;Laas et al, 2017;Ottenhof et al 2018). While reduced gray matter volumes in limbicprefrontal regions have been consistently reported in psychiatric disorders characterized by exaggerated anxiety and deficient emotion regulation (van Tol et al 2010;Bora et al 2012;Ahmed-Leitao et al 2016), associations between emotional functioning and limbic-prefrontal volumes in healthy subjects remain less clear, such that elevated anxiety has been associated with both, volumetric increases as well as decreases in this circuitry (e.g.…”
Section: Discussionmentioning
confidence: 99%